Vitamin D protects against high glucose-induced pancreatic β-cell dysfunction via AMPK-NLRP3 inflammasome pathway. (1st May 2022) - Wu, Mian; Lu, Li; Guo, Kaifeng; Lu, Junxi; Chen, Haibing
Abstract: Vitamin D deficiency is considered a pandemic and has been postulated to increase the risk of type 2 diabetes mellitus (T2DM). Activation of nod-like receptor protein 3 (NLRP3) signaling induced by hyperglycemia stress has been recognized as a key priming stage for pancreatic β-cell inflammation in T2DM pathogenesis. AMP-activated protein kinase (AMPK) activation attenuates NLRP3 inflammasome upregulation in diabetes. This study investigated whether vitamin D3 could protect cells against high glucose-induced inflammation by modulating this critical step. A human cross-sectional study of 78 healthy, glucose-tolerant volunteers and 399 patients with type 2 diabetes was undertaken. The relationship between serum 25(OH)D3 levels and β-cell function was assessed using Pearson correlation analysis and multiple linear regression, and a high-glucose diet-induced rat model of impaired glucose tolerance was used to evaluate the effects of cholecalciferol. Intraperitoneal glucose tolerance tests and an ELISA were performed to detect the function of pancreatic islets. Glucose-stimulated insulin secretion, pyroptosis, reactive oxygen species (ROS) production, and NLRP3 pathway were evaluated together to determine the role of vitamin D in high glucose-induced pancreatic β-cell dysfunction in INS-1E cells. The clinical results showed a positive association between serum 25(OH)D3 levels and β-cell function in male patients with type 2 diabetes. In vivo, cholecalciferol significantly reduced blood glucose levels and improved insulin secretion in response to glucose loading in the high glucose diet-induced rat model. In vitro studies have demonstrated that 1, 25(OH)2 D3 promotes insulin release in both islets and INS-1E cells. Mechanistically, our results demonstrated that vitamin D3 can activate AMPK, inhibiting the mTOR pathway, thus inhibiting NLRP3 inflammasome activation and alleviating pyroptosis in β-cell dysfunction. This study showed that vitamin D protects against high-glucose-induced β-cell dysfunction by enhancing the AMPK pathway, thereby suppressing NLRP3 inflammasome activation. Highlights: Serum 25(OH)D3 levels were positively correlated with β-cell function in male patients with type 2 diabetes. Cholecalciferol reduced blood glucose levels and improved insulin secretion in high glucose diet-induced rat model. Vitamin D protects against high-glucose-induced β-cell dysfunction by regulating the AMPK/NLRP3 inflammasome pathway.